2017
DOI: 10.1017/s135246581700056x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Anxiety in Multiple Sclerosis: A Replication and Treatment Case Series

Abstract: Given the high rates of HA in MS patients and its impact on QoL, this case series suggests that a brief CBT intervention could significantly improve patients' wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Mansourzadeh et al also showed that acupressure reduces anxiety [17]. The results of Dehghan Mehr et al and Ganak et al are also consistent with our results [18,19]. Howeevr, Vali et al's study showed that acupressure does not reduce preoperative anxiety [20].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Mansourzadeh et al also showed that acupressure reduces anxiety [17]. The results of Dehghan Mehr et al and Ganak et al are also consistent with our results [18,19]. Howeevr, Vali et al's study showed that acupressure does not reduce preoperative anxiety [20].…”
Section: Resultssupporting
confidence: 90%
“…In Iran, the prevalence of stress and anxiety is 44.8% and 39.1%m respectively [13]. Stress and anxiety aggravate the symptoms of MS and reduce the quality of life of these patients [15,16,19,20]. People with MS usually do not use anti-stress and anti-anxiety medications due to side effects and financial costs [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…If, as is possible, health anxiety is to some extent driving distress and disability experienced, then it is possible that treatment that seeks to reduce such anxiety may be helpful. This study has been replicated and, in a consecutive single case series, health anxiety was substantially reduced in four out of five patients with RRMS (Carrigan et al, 2016). We have since sought to replicate this work in patients with Parkinson's disease, where both cognitive and physical impairment was evident, obtaining similar results in terms of the perception of cognitive impairment (Fixter et al, 2016).…”
Section: Long-term Conditionsmentioning
confidence: 67%
“…In emotional disorders, neuroticism has been considered a key etiology mechanism shared by all emotional disorders [ 20 ]. Other mechanisms identified have been rumination, suppression, anxiety sensitivity, and misappraisal [ 21 ], frequently reported in PwMS [ 22 ]. These mechanisms can increase or maintain persistent negative emotions and may affect physical and psychological functioning.…”
Section: Introductionmentioning
confidence: 99%